ANALYSIS IMPLEMENTATIONS OF MATERNAL AND NEONATAL REFERAL NETWORK INFORMATION AT PUSKESMAS TANAH TINGGI TANGERANG BANTEN - Fery Ferdiansyah; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
One of the efforts to reduce the maternal mortality rate (MMR) is to adopt the EMAS (Expanding Maternal And Neonatal Survival) program SIJARIEMAS (Information System for Maternal and Neonatal Referrals in the prevention of '3 Too Late. This study aims to obtain an overview of the implementation of SIJARIEMAS in terms of sources. Human resources, the availability of facilities and infrastructure, as well as procedures at the Tanah Tinggi Public Health Center. The research was carried out using the Rapid Assessment Procedure (RAP), a technique of collecting data using a quick assessment to obtain in-depth and relatively brief information. These are Doctors on Watch, Midwives, and Nurses. The data were collected with 3 focus group discussions. The data were analyzed descriptively. The results showed that officers still found it difficult to refer patients to the hospital due to the long response of the SIJARIEMAS Call Center in finding a hospital. There are still officers who do not follow the referral soup. Obstacles faced by officers in making emergency referrals resulted in delays in handling that could lead to death. Conclusion: SIJARIEMAS makes referrals easier, but the response of the old SIJARIEMAS call center, Puskesmas officers, still deviates from the SIJARIEMAS procedure. Efforts are needed to improve call center response and services by Puskesmas officers.